PtrWOX13A Promotes Wood Formation and Bioactive Gibberellins Biosynthesis in Populus trichocarpa - Zhang, Yang; Liu, Yingying; Wang, Xueying; Wang, Ruiqi; Chen, Xuebing; Wang, Shuang; Wei, Hairong; Wei, Zhigang (Frontiers in Plant Science, 2022)
WUSCHEL-related homeobox (WOX) genes are plant-specific transcription factors (TFs) involved in multiple processes of plant development. However, there have hitherto no studies on the WOX TFs involved in secondary cell wall (SCW) formation been reported. In this study, we identified a Populus trichocarpa WOX gene, PtrWOX13A, which was predominantly expressed in SCW, and then characterized its functions through generating PtrWOX13A overexpression poplar transgenic lines; these lines exhibited not only significantly enhanced growth potential, but also remarkably increased SCW thicknesses, fiber lengths, and lignin and hemicellulose contents. However, no obvious alternation in cellulose content was observed. We revealed that PtrWOX13A directly activated its target genes through binding to two cis-elements, ATTGATTG and TTAATSS, in their promoter regions. The fact that PtrWOX13A responded to the exogenous GAs implies that it is responsive to GA homeostasis caused by GA inactivation and activation genes (e.g., PtrGA20ox4, PtrGA2OX1, and PtrGA3OX1), which were regulated by PtrWOX13A directly or indirectly. Since the master switch gene of SCW formation, PtrWND6A, and lignin biosynthesis regulator, MYB28, significantly increased in PtrWOX13A transgenic lines, we proposed that PtrWOX13A, as a higher hierarchy TF, participated in SCW formation through controlling the genes that are components of the known hierarchical transcription regulation network of poplar SCW formation, and simultaneously triggering gibberellin-mediated signaling cascade. The discovery of PtrWOX13A predominately expressing in SCW and its regulatory functions in the poplar wood formation has important implication for improving wood quality of trees via genetic engineering.